2015
DOI: 10.3390/e17042140
|View full text |Cite
|
Sign up to set email alerts
|

Deep Belief Network-Based Approaches for Link Prediction in Signed Social Networks

Abstract: In some online social network services (SNSs), the members are allowed to label their relationships with others, and such relationships can be represented as the links with signed values (positive or negative). The networks containing such relations are named signed social networks (SSNs), and some real-world complex systems can be also modeled with SSNs. Given the information of the observed structure of an SSN, the link prediction aims to estimate the values of the unobserved links. Noticing that most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 32 publications
0
29
0
1
Order By: Relevance
“…The experimental data revealed that the proposed method outperformed approaches that rely on topological features alone. Several link prediction approaches that are based on a deep belief network were presented in [12]. The results obtained from the experiments on datasets collected from different sources revealed that the methods effectively predicted link values and exhibited a remarkable generalization capability among the studied datasets.…”
Section: Predicting Links In Snmentioning
confidence: 99%
“…The experimental data revealed that the proposed method outperformed approaches that rely on topological features alone. Several link prediction approaches that are based on a deep belief network were presented in [12]. The results obtained from the experiments on datasets collected from different sources revealed that the methods effectively predicted link values and exhibited a remarkable generalization capability among the studied datasets.…”
Section: Predicting Links In Snmentioning
confidence: 99%
“…This is the step of model training or pdf estimation. Among all combination methods, there is an inevitable time complexity, that is to obtain the similarity matrix or final link prediction scores according to Equation (14). This step requires time O(d•n s •N 2 ).…”
Section: Complexity Analysismentioning
confidence: 99%
“…At the same time, similarity index fusion methods are springing up [7,8]. Recent years, with the development of deep learning, some deep features extraction methods have been proposed [9,10], the fusion of structure and attribute information has been attached importance again [11][12][13][14]. These methods have strong consistency.…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian network has been also considered as a consistent model to understand the relations between future links to be predicted in networks [19], [20]. Recently, negative link prediction in social networks has attracted the attention of many researchers and considerable research work is being carried out to find efficient techniques for the same [15], [16], [18]. Such techniques aim to perform link prediction across multiple signed networks.…”
Section: Introductionmentioning
confidence: 99%